PENILAIAN RISIKO KESEHATAN KERJA PADA USAHA MIKRO WARUNG TEGAL “BERKARYA” - Silitonga, Yunico Samuel M.; Fitri, Zayanda; Dhiyaputri K., Anjani; Hendratno, Ergita Fujasari; Ahadysta, Kennygya; Puryani, Noorma Zuliana; Hikmah, Wulan Nur; Lestari, Ade Dwi (Universitas Trisakti, 2024)
Pengabdian kepada Masyarakat di warung tegal